2006
DOI: 10.1097/01.smj.0000215855.98512.9d
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mucosa-associated Lymphoid Tissue (MALT) Lymphoma Occurring in the Rectum: A Case Report and Review of the Literature

Abstract: The primary extranodal B-cell lymphoma of mucosa-associated lymphoid tissue (MALT) is a distinct clinical pathologic entity that develops in diverse anatomic locations such as the stomach, salivary gland, thyroid, lung, and breast; however, colorectal involvement is rare. To the best of our knowledge, only 30 cases of primary rectal MALT lymphoma have been published in the English language literature, mostly from Japan. A single case has been reported from the US before this report. The most common symptoms ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
0
39
0
1
Order By: Relevance
“…10 In the present case, H. pylori infection was not confirmed. Thus, the eradication of H. pylori was not attempted.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…10 In the present case, H. pylori infection was not confirmed. Thus, the eradication of H. pylori was not attempted.…”
mentioning
confidence: 67%
“…8,9 Most MALT lymphomas arise from the gastrointestinal organs. 10 However, it is able to develop in diverse anatomic locations such as the salivary gland, thyroid, lung and breast. 9,10 A relationship between gastric MALT lymphoma and Helicobacter pylori (H. pylori) infection has been clearly established, and low grade gastric MALT lymphoma is known to regress after eradication of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a standard treatment protocol for colonic MALT lymphoma has yet to be established because of the rarity of the disease and lack of an established etiological cause. Treatments for colonic MALT lymphoma include surgery, chemotherapy, radiotherapy and endoscopic resection (13). In 1997, Matsumoto et al reported the first case of rectal MALT lymphoma regression after H. pylori eradication therapy (14).…”
Section: Discussionmentioning
confidence: 99%
“…Primary rectal MALT lymphomas are even rarer, therefore, their treatment has not been well-studied and there is no established standard therapy. Recent reports have documented the disappearance of rectal MALT lymphomas following H. pylori eradication therapy [5][6][7][8][9][10][11][12][13][14][15][16], however, this remains controversial, and it is yet to be clarified whether complete histological disappearance of rectal MALT lymphomas can be achieved following H.pylori eradiation therapy, since all previous reports are based on evaluation of only the endoscopic findings. We performed ESD and evaluated the disappearance of the lesions histopathologically.…”
Section: Introductionmentioning
confidence: 99%